Pengaruh Kepemimpinan Terhadap Disiplin Kerja Aparatur Sipil Negara (ASN) Dinas Perhubungan Kab. Garut - Paroli, Paroli (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to determine the influence of leadership on the work discipline of State Civil Apparatus (ASN) in the Garut Regency Transportation Service. The research method used is quantitative with data analysis techniques using the Spearman Rank correlation coefficient test and determination test. Data was obtained from the Garut Regency Transportation Service through interviews, questionnaires, observations and literature studies. The research results show that there is a positive and significant influence between leadership and ASN work discipline, with a Spearman Rank correlation coefficient of 0.821. The determination test shows that leadership's contribution to work discipline is 67.4%, while 32.6% is influenced by other factors. Hypothesis analysis using the t test confirms that leadership has a positive and significant effect on work discipline. The conclusion of this research shows that effective leaders can influence the level of work discipline of ASNs in the Garut Regency Transportation Service. The implication is that increasing leadership is expected to improve work discipline and organizational performance. However, other factors such as motivation, incentives and personal abilities also need to be considered in strategic planning for the development of sustainable work discipline. Keywords: Leadership, Work Discipline, Garut Regency Transportation Service ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh kepemimpinan terhadap disiplin kerja Aparatur Sipil Negara (ASN) di Dinas Perhubungan Kabupaten Garut. Metode penelitian yang digunakan adalah kuantitatif dengan teknik analisis data menggunakan uji koefisien korelasi Rank Spearman dan uji determinasi. Data diperoleh dari Dinas Perhubungan Kabupaten Garut melalui wawancara, kuesioner, observasi, dan studi pustaka. Hasil penelitian menunjukkan adanya pengaruh positif dan signifikan antara kepemimpinan dan disiplin kerja ASN, dengan koefisien korelasi Rank Spearman sebesar 0,821. Uji determinasi menunjukkan kontribusi kepemimpinan terhadap disiplin kerja sebesar 67.4%, sementara 32.6% dipengaruhi oleh faktor-faktor lain. Analisis hipotesis dengan uji t menegaskan bahwa kepemimpinan berpengaruh positif dan signifikan terhadap disiplin kerja. Kesimpulan penelitian ini menunjukkan bahwa pemimpin yang efektif dapat memengaruhi tingkat disiplin kerja ASN di Dinas Perhubungan Kabupaten Garut. Implikasinya, peningkatan kepemimpinan diharapkan dapat meningkatkan disiplin kerja dan kinerja organisasi. Meski demikian, faktor lain seperti motivasi, insentif, dan kemampuan personal juga perlu diperhatikan dalam perencanaan strategis untuk pengembangan disiplin kerja yang berkelanjutan.